2003
DOI: 10.1093/ndt/gfg034
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of autoantibody production by mycophenolate mofetil: effects on the development of SLE in (NZBxNZW)F1 mice

Abstract: The mechanisms through which MMF controls the development of SLE in (NZB x NZW)F(1) females is highly dependent upon immunosuppressor dose. Interestingly, lower dose MMF selectively reduced IgG2a antibody levels, suggesting that this dose may modulate T(H1) CD4+ activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…Equivalent dosing of free MPA at 0.625 mpk did not extend survival, nor did 16-fold more of free drug at 10 mpk. These results demonstrate the therapeutic advantage of using nanoparticles, as published reports have shown that much larger and more frequent free MPA regimens of 30 to 100 mpk every day are used for treating murine lupus (34,35).…”
Section: Figuresupporting
confidence: 70%
“…Equivalent dosing of free MPA at 0.625 mpk did not extend survival, nor did 16-fold more of free drug at 10 mpk. These results demonstrate the therapeutic advantage of using nanoparticles, as published reports have shown that much larger and more frequent free MPA regimens of 30 to 100 mpk every day are used for treating murine lupus (34,35).…”
Section: Figuresupporting
confidence: 70%
“…Moreover, (NZBϫNZW)F 1 female mice treated with sirolimus showed a moderate, but nonsignificant, increase in serum IgG1 antibodies at the end of 27 weeks of age; a similar effect had previously been described after treatment of (NZBϫNZW)F 1 female mice with low doses of mycophenolate mofetil. 15 This moderate increase in IgG1 could be related to their protective effect against SLE development in (NZBϫNZW)F 1 female mice. In this sense, the role of T-cells in the pathogenesis of SLE in (NZBϫNZW)F 1 mice has been underlined in several studies.…”
Section: Discussionmentioning
confidence: 94%
“…This suggestion is corroborated by experimental findings in Fas lpr/lpr l upus-prone mice. [41][42][43][44][45] Induction therapy One randomized controlled trial compared mycophenolate mofetil for 12 months with oral cyclophosphamide for 6 months followed by azathioprine for 6 months (both groups also received prednisolone) in 42 Chinese patients with active class IV lupus nephritis. 46 After 12 months, response rates in the two groups were similar, with approximately 80% and 15% of patients achieving complete and partial remission, respectively (Table 1).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%